Correction: Critical advances for the iron molten air battery: a new lowest temperature, rechargeable, ternary electrolyte domain. Issue 46 (9th November 2016) - Liu, Shuzhi; Li, Xin; Cui, Baochen; Liu, Xianjun; Hao, Yulan; Guo, Qi; Xu, Peiqiang; Licht, Stuart
Abstract : Correction for 'Critical advances for the iron molten air battery: a new lowest temperature, rechargeable, ternary electrolyte domain' by Shuzhi Liu et al., J. Mater. Chem. A, 2015, 3, 21039–21043.